The Relationship of Risk Factors to the Incidence of Type II Diabetes Mellitus in Pre-Elderly and Elderly (Study in Ternate City) - Permana, Dini Rahmawati; The, Fera; Athallah, Nadhif; Jansen, Gomgom (AIBPM Publisher, 2023)
The purpose of this study is to clarify the relationship between risk factors to the incidence of type two diabetes mellitus in the pre-elderly and elderly in Ternate City. This research uses a cross-sectional study and uses univariate and bivariate analyzes to determine the relationship of factors with diabetes mellitus in pre-elderly and elderly. Samples were selected by a cluster random sampling technique. Data collection measures take the form of questionnaires with structured questions. This study was conducted on pre-elderly and elderly aged above 45 in the public health center (PUSKESMAS) in Ternate City, which amounted to 299 respondents. The results showed eight interesting findings. One of them is there was a significant relationship between age and the incidence of diabetes mellitus. Moreover, there was no significant relationship between sex and the incidence of diabetes mellitus.